Hyper-activation of Aurora kinase a-polo-like kinase 1-FOXM1 axis promotes chronic myeloid leukemia resistance to tyrosine kinase inhibitors - M. Mancini (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Chronic myeloid leukemia (CML) is a myeloproliferative disease caused by the constitutive tyrosine kinase (TK) activity of the BCR-ABL1 fusion protein. Accordingly, TK inhibitors have drastically changed the disease prognosis. However, persistence of the transformed hematopoiesis even in patients who achieved a complete response to TK inhibitors and the disease relapse upon therapy discontinuation represent a major obstacle to CML cure. Methods Thiostrepton, Danusertib and Volasertib were used to investigate the effects of FOXM1, AKA and Plk1 inhibition in K562-S and K562-R cells. Apoptotic cell death was quantified by annexin V/propidium iodide staining and flow cytometry. Quantitative reverse transcription (RT)-PCR was used to assess BCR-ABL1, FOXM1, PLK1 and AURKA expression. Protein expression and activation was assessed by Western Blotting (WB). Clonogenic assay were performed to confirm K562-R resistance to Imatinib and to evaluate cells sensitivity to the different drugs. Results Here we proved that BCR-ABL1 TK-dependent hyper-activation of Aurora kinase A (AURKA)-Polo-like kinase 1 (PLK1)-FOXM1 axis is associated with the outcome of Imatinib (IM) resistance in an experimental model (K562 cell line) and bone marrow hematopoietic cells. Notably, such a biomolecular trait was detected in the putative leukemic stem cell (LSC) compartment characterized by a CD34+ phenotype. Constitutive phosphorylation of FOXM1 associated with BCR-ABL1 TK lets FOXM1 binding with β-catenin enables β-catenin nuclear import and recruitment to T cell factor/lymphoid enhancer-binding factor (TCF/LEF) transcription complex, hence supporting leukemic cell proliferation and survival. Lastly, the inhibition of single components of AURKA-PLK1-FOXM1 axis in response to specific drugs raises the expression of growth factor/DNA damage-inducible gene a (GADD45a), a strong inhibitor of AURKA and, as so, a critical component whose induction may mediate the eradication of leukemic clone. Conclusions Our conclusion is that AURKA, PLK1 and FOXM1 inhibition may be considered as a promising therapeutic approach to cure CML.